Sonar detection amphibious vehicle - Toha, Siti Fauziah; Ayub, Abdul Mu’izz; Zainol, Zakariya (2012)
Engineering Emergency management (pre-disaster occurrence) and first response information (post-disaster occurrence) are crucial during disaster attack as time is of the essence of life. The study on this field is vital especially in Malaysia, which located at the south-east Asia region, within the link of natural disaster area. This paper presents the conceptual design of an amphibious vehicle consisted of several features that will assist the savior in giving hands to help the victims of the disaster. The designed sonar detection amphibious vehicle is called SOPHIBIAN. A SOPHIBIAN vehicle is provided with Global Positioning System (GPS) as it will control manually form the central unit through wireless communication. The GPS will provide information regarding the current position of the vehicle. Camera also is used to assist the movement of the vehicle and also to detect for any moving objects or victims during the disaster. Obstacles avoidance will be one of the main factors of using the camera. For underwater operation, ultrasonic sensor will acts as sonar detector to detect any victims inside the water. The overall design prototype of the vehicle also very important as it can travel along muddy terrain.